DETERMINATION OF DOWRY BASED ON THE BRIDE'S EDUCATIONAL LEVEL REVIEWED ACCORDING TO ISLAMIC LAW: Case Study in Jaya District, Aceh Jaya Regency - Muliana, Muliana (Al-Iqtishadiah: Jurnal Hukum Ekonomi Syariah, 2023)
A dowry is a gift that is required for a prospective husband to a prospective wife in marriage, whether in the form of gold, money or useful items mentioned during the marriage contract which are the rights of the woman (wife) in the marriage. In the practice of the people of Jaya District, Aceh Jaya Regency, the dowry is determined according to the educational level of the prospective bride. The problem and aim of this research is to find out the factors that cause the people of Jaya District, Aceh Jaya Regency to determine the dowry based on the bride's education level, to find out the view of Islamic law regarding determining the dowry based on the bride's education level. To obtain an answer to this, in this research the author used the Field Research method to draw conclusions using descriptive analytical research, namely explaining in detail the facts found in the field or in society, then analyzing them again to obtain conclusions regarding the problem. in this research. The results of the research show that the determination of the dowry in the traditions of the people of Jaya District, Aceh Jaya Regency is carried out by looking at the educational level of the bride to be married. Because the position and function of dowry in Jaya District society is a new tradition that can give pride to parents (guardians), future wives and symbolizes a woman's success. Determining the dowry or jeulamei which is based on the education level of the bride in Jaya District, has two legal consequences, namely, if the determination of the dowry based on the woman's education is carried out with the aim of increasing the dignity of women, then it is legal or lawful for them to accept it, but on the contrary, if the determination The dowry or jeulamei is because you want to boast and burden the man or future husband, thereby causing things that are contrary to the Shari'a. This is something that religion does not like very much.